Viral rescue of magnocellular vasopressin cells in adolescent Brattleboro rats ameliorates diabetes insipidus, but not the hypoaroused phenotype - Schatz, Kelcie; Grinevich, Valéry (Scientific reports, 2019)
Dysregulated arousal often accompanies neurodevelopmental disorders such as attention deficit hyperactivity disorder and autism spectrum disorder. Recently, we have found that adolescent homozygous Brattleboro (Hom) rats, which contain a mutation in the arginine vasopressin (AVP) gene, exhibit lower behavioral arousal than their heterozygous (Het) littermates in the open field test. This hypoaroused phenotype could be due to loss of AVP in magnocellular cells that supply AVP to the peripheral circulation and project to limbic structures or parvocellular cells that regulate the stress axis and other central targets. Alternatively, hypoarousal could be a side effect of diabetes insipidus - polydipsia and polyuria seen in Hom rats due to loss of AVP facilitation of water reabsorption in the kidney. We developed a viral-rescue approach to “cure” magnocellular AVP cells of their Brattleboro mutation. Infusion of a recombinant adeno-associated virus (rAAV) containing a functional Avp gene and promoter (rAAV-AVP) rescued AVP within magnocellular cells and fiber projections of the paraventricular nucleus of the hypothalamus (PVN) of male and female adolescent Hom rats. Furthermore, water intake was markedly reduced, ameliorating the symptoms of diabetes insipidus. In contrast, open field activity was unaffected. These findings indicate that the hyporaoused phenotype of adolescent Hom rats is not due to the loss of AVP function in magnocellular cells or a side effect of diabetes insipidus, but favors the hypothesis that central, parvocellular AVP mechanisms underlie the regulation of arousal during adolescence.
Gesehen am 22.08.2019